Saminbot: a virtual assistant to collect data during the COVID-19 pandemic - Vera Olivera, Harley (2021)
The lack of datasets to make decisions in quick actions during the pandemic caused by COVID-19 showed the need to use new technologies to speed up the process of capturing decentralized information. In this article, we present a virtual assistant (chatbot) called SaminBot, as an alternative to collect data and provide information during the COVID-19 pandemic; this chatbot opperated in the Cusco region of Peru with conversations in the areas of health, economy, and education from January to August 2020. “SaminBot” starts data collection based on the user’s area of interest, obtains demographic information, and guides him through questions to provide helpful information according to his situation. Specialists validated the questionariess. Data gathering was performed from January to June 2021 through WhatsApp and Facebook Messenger platforms and the project’s website, where 1586 records were obtained.